If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2t = -13 Solving 2t = -13 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Divide each side by '2'. t = -6.5 Simplifying t = -6.5
| 16s^2+24s+9= | | 3(2)+6(8+2)= | | B+10.8=12.80 | | 10=s/2+78 | | 1/3x=6-1/5x | | 3x+2(x+1)=6x+(3x-4) | | 7n-20=-48 | | c^2+14c+45= | | m^2+6m+4=-4 | | 4i(6+2i)= | | y=3.0x+1.7 | | 6x+3=12-2x | | t(5t+2)= | | 276/12 | | Y=6x^2+x-15 | | -(-21y+29)-21y=-(19y+23)+26 | | 4m+6m+7m= | | 81w^2-49= | | -(67r+8s+61)= | | 5(3-y)/3=y-5 | | X^2-13x-168= | | 2x-1=y+4 | | 16-5(3p-4)=8(-2p+11) | | 9=3(5q-2) | | -6x+3(3)= | | X+8=4(X-10) | | -4x-6=-42 | | x/2-5=6 | | (1/3)x=1017 | | 120+x^2-200+11x=100 | | 2x+2=3x-ray | | x^2-14x=-53 |